(untitled) (Asian Journal of Agriculture, 2024)
Abstract. Ebrahim MS, Bisetegn KB, Tedla YR, Tufa MT. 2024. Evaluation of the yield and agronomic trait performance of BC2F2 common bean lines at Hawassa, Ethiopia. Asian J Agric 8: 50-56. The common bean is the most important legume in Ethiopia and is grown mainly for domestic consumption, export and as a source of protein. Farmers in the study area are still producing old varieties; therefore, the production decreases in the area, even though there are suitable environments for common bean production. Bean anthracnose is one of the major constraints that challenged the production of common bean in the study area. To address the above gap, to identify introgressed bean lines for anthracnose resistance with improved agronomic traits that were developed through backcross breeding program using pot experiments under screen house conditions. Twelve common bean genotypes, including eight developed BC2F2 lines, two parental lines, and two cultivars, were used to evaluate agronomic performance. Data on seven quantitative traits and three qualitative traits were collected from each tagged tested material. Analysis of variance revealed a highly significant difference (p<0.001) in the agronomic traits of the BC2F2 line under screen house conditions. As a result, four BC2F2 lines (Plant-3, Plant-5, Plant-9, and Plant 15) exhibited significantly greater differences in the most important agronomic traits than the remaining studied plant materials. In the end, two lines identified to have better agronomic performance (Plant-3 and Plant-15) were selected and promoted for the future to be used for production after verifying in multiple locations for the study and similar agro-ecologies. The results will contribute to an increase in the production of this important crop under farmer conditions. They will significantly benefit and impact Ethiopia’s regional and national common bean improvement programs.